Understanding low-value care and associated de-implementation processes: a qualitative study of Choosing Wisely Interventions across Canadian hospitals - Gillian Parker; Monika Kastner; Karen Born; Nida Shahid; Whitney Berta (BMC, 2022)
Abstract Background Choosing Wisely (CW) is an international movement comprised of campaigns in more than 20 countries to reduce low-value care (LVC). De-implementation, the reduction or removal of a healthcare practice that offers little to no benefit or causes harm, is an emerging field of research. Little is known about the factors which (i) sustain LVC; and (ii) the magnitude of the problem of LVC. In addition, little is known about the processes of de-implementation, and if and how these processes differ from implementation endeavours. The objective of this study was to explicate the myriad factors which impact the processes and outcomes of de-implementation initiatives that are designed to address national Choosing Wisely campaign recommendations. Methods Semi-structured interviews were conducted with individuals implementing Choosing Wisely Canada recommendations in healthcare settings in four provinces. The interview guide was developed using concepts from the literature and the Implementation Process Model (IPM) as a framework. All interviews were conducted virtually, recorded, and transcribed verbatim. Data were analysed using thematic analysis. Findings Seventeen Choosing Wisely team members were interviewed. Participants identified numerous provider factors, most notably habit, which sustain LVC. Contrary to reporting in recent studies, the majority of LVC in the sample was not 'patient facing'; therefore, patients were not a significant driver for the LVC, nor a barrier to reducing it. Participants detailed aspects of the magnitude of the problems of LVC, providing insight into the complexities and nuances of harm, resources and prevalence. Harm from potential or common infections, reactions, or overtreatment was viewed as the most significant types of harm. Unique factors influencing the processes of de-implementation reported were: influence of Choosing Wisely campaigns, availability of data, lack of targets and hard-coded interventions. Conclusions This study explicates factors ranging from those which impact the maintenance of LVC to factors that impact the success of de-implementation interventions intended to reduce them. The findings draw attention to the significance of unintentional factors, highlight the importance of understanding the impact of harm and resources to reduce LVC and illuminate the overstated impact of patients in de-implementation literature. These findings illustrate the complexities of de-implementation.